Management of Diarrhea in Young Children in Sub-Saharan Africa: Adherence to World Health Organization Recommendations During the Global Enteric Multisite Study (2007–2011) and the Vaccine Impact of Diarrhea in Africa (VIDA) Study (2015–2018). (19th April 2023) - Deichsel, Emily L; Keita, Adama Mamby; Verani, Jennifer R; Powell, Helen; Jamka, Leslie P; Hossain, M Jahangir; Jones, Joquina Chiquita M; Omore, Richard; Awuor, Alex O; Sow, Samba O; Sanogo, Doh; Tapia, Milagritos D; et al.
Abstract: Background: Reducing diarrhea-related morbidity and mortality is a global priority, particularly in low-resource settings. We assessed adherence to diarrhea case management indicators in the Global Enteric Multisite Study (GEMS) and Vaccine Impact of Diarrhea in Africa (VIDA) study. Methods: GEMS (2007–2010) and VIDA (2015–2018) were age-stratified case-control studies of moderate-to-severe diarrhea (MSD) in children aged <5 years. In this case-only analysis, we included children enrolled in The Gambia, Kenya, and Mali. A case with no dehydration received adherent care at home if they were offered more than usual fluids and at least the same as usual to eat. Children with diarrhea and some dehydration are to receive oral rehydration salts (ORS) in the facility. The recommendation for severe dehydration is to receive ORS and intravenous fluids in the facility. Adherent care in the facility included a zinc prescription independent of dehydration severity. Results: For home-based management of children with MSD and no signs of dehydration, 16.6% in GEMS and 15.6% in VIDA were adherent to guidelines. Adherence to guidelines in the facility was likewise low during GEMS (some dehydration, 18.5%; severe dehydration, 5.5%). The adherence to facility-based rehydration and zinc guidelines improved during VIDA to 37.9% of those with some dehydration and 8.0% of children with severe dehydration. Conclusions: At research sites in The Gambia, Kenya, and Mali, suboptimal adherence to diarrhea case management guidelines for children aged <5 years was observed. Opportunities exist for improvement in case management for children with diarrhea in low-resource settings. Abstract : We assessed adherence to World Health Organization Integrated Management of Childhood Illnesses guidelines for the treatment of diarrhea in sub-Saharan African children enrolled in the Global Enteric Multisite Study and Vaccine Impact of Diarrhea in Africa study.